Assessing gender discrimination via female employee proportion and firm profits evidence from Philippine firm-level data - Altarejos, Caesar III S.; Cheng, Lance Bentley C.; Alburo, Florian (Quezon City School of Economics, University of the Philippines Diliman, 2021)
In 2020, the World Economic Forum released its annual Gender Gap Report which is published to detail the gap between men and women around the world based on four key indicators: economic participation and opportunity, educational attainment, health and survival, and political empowerment. The Philippines ranked 16th out of 153 countries in the 2020 edition which is a far cry from its ranking of 6th in the report's first release back in 2006. However, a major point of interest is the Philippine's economic participation and opportunity score. At 14th highest in the world, this is the country's highest ranking relative to the other countries out of the 4 key indicators in the report. One then begs to ask the question: with the Philippines being in the top 15 countries when it comes to equality in labor opportunities for both genders, does discrimination in the labor force still exist? To answer this question. we take a look at firm-level data within the country particularly the 2009 and 2015 editions of the Enterprise Survey from the World Bank. By modeling this study after Hoang and Huynh (2020) who extends the works of Arrow (1973), Becker (1971) and Goldberg (1982), we were able to create a profit ratio equation which is conditioned on the individual firm's gender proportion in their labor force. We then run three different OLS regression models to test the relationship of the profit ratio with gender proportion in the workforce among other things. In 2015, our baseline model showed some evidence of discrimination towards females and that the proportion of female workers does have a negative effect on the firm's profit ratio. However, due to the limited number of observations in 2015, we are unable to
conclude this. Moreover, when decomposing the female labor force into production and non-production, skilled and unskilled, or combinations of the two, we find that there is no evidence of gender discrimination. Lastly, like Hoang's study on the Vietnamese labor force, firm characteristics have a significant impact on gender discrimination. Our results showed that export oriented firms and FIES exhibited lower profit rates when combined with an increased proportion of female labor. These insights are used to help further studies on gender in the labor force with the goal of creating policies that will further level the playing field and provide equal opportunities for both genders in the future.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: Sex discrimination against women -- Philippines